CLINICAL AND IMMUNOLOGICAL CHARACTERISTICS IN CHILDREN WITH PSORIASIS (Eureka Journal of Health Sciences & Medical Innovation, 2026)
In recent years, cytokines have been recognized as crucial mediators in the regulation of immunopathological mechanisms, particularly in allergic responses. This study aims to evaluate the immunological profile of children with psoriasis. A significant proportion of patients exhibited a burdened allergic history and elevated IgE levels. It appears that the clinical severity of psoriasis is determined not merely by serum IgE concentration, but by the influence of specific triggers on the development of allergic inflammation. These findings provide a better understanding of immune system functional disorders in pediatric psoriasis and can be utilized to improve therapeutic management.
Keywords: Psoriasis, children, allergy, cytokines, immunity, immunopathogenesis, interleukins.